Biological Activity of Der p 1 and Der f 1 in Allergic Asthma and Their Contribution in Inflammation and the Role of Anti-inflammation in Allergic Asthma - Julian; Rozaliyani, Anna; Wibowo, Heri; Damayanti, Triya (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Asthma is a disease marked by chronic inflammation of the airways, with indications including wheezing, shortness of breath, and/or cough. As reported by GINA, the global prevalence of asthma is 1-18%. One type of asthma is Allergic asthma which is triggered by allergens, like Der p 1 and Der f 1 which upregulate type II immune response to secret IL-4 and IL-13 to upregulate IgE secretion. IgE binds to FcÎµRI in mast cells to release mediators that cause hypercontraction, this condition leads to asthma. Meanwhile, anti-inflammatory IL-10 manages IgE production by reducing inflammatory cytokine production and changing isotype switching. IgE Production is a crucial step. Therefore, it is essential to explore the cellular and molecular factors that trigger the regulated isotype-switching IgE and its suppressed mechanism, so this review will explore the biological activity of Der p 1 and Der f I and their contribution to inflammation and the role of anti-inflammation in allergic asthma especially isotype switching IgE We used PRISMA approaches, and tools (RSCB PDB, Uniprot, and SMART). The result appeared Der p 1, and Der f 1 activity have impacts on IL-4, IL-13, IL-10, and IgE secretion.